Upper atmosphere of Mars up to 120 km: Mars Global Surveyor accelerometer data analysis with the LMD general circulation model - Angelats Coll, M; Forget, F; López-Valverde, M; Read, P; Lewis, SR (2004)
Mars Global Surveyor (MGS) aerobraking accelerometer density measurements are analyzed with the use of the general circulation model (GCM) at the Laboratoire de Météorologie Dynamique (LMD). MGS constant altitude density data are used, obtaining longitudinal wavelike structures at fixed local times which appear to be dominated by low zonal wave number harmonics. Comparisons with simulated data for different seasons and latitudinal bands at constant altitude are performed. Excellent agreement is obtained between the simulated and observational data for low latitudes, with accuracy in both mean and zonal structure. Higher latitudes show a reduction in agreement between GCM results and MGS data. Comparisons that result in good agreement with the observational data allow for the study of wave composition in the MGS data. In particular, the excellent agreement between the simulations and the data obtained at 115 km during areocentric longitude Ls ≈ 65° allows the extraction of the major contributors to the signature, with the eastward propagating diurnal waves of wave numbers one to three being the major players. Significant contributions are also obtained for eastward propagating semidiurnal waves of wave numbers two, three, and five and diurnal wave number five. A sensitivity study is performed to delineate the effects of the near-IR tidal forcing of the upper atmosphere on the wave content at those heights. Simulations without this forcing yield reduced amplitudes for diurnal eastward propagating waves two and three along with a more latitudinally symmetric response for these two components as well as for diurnal eastward propagating wave number one. Copyright 2004 by the American Geophysical Union.